Pembentukan Moral: Implementasi Nilai Pancasila Dan Pengaruhnya Terhadap Siswa SD Harapan 2 Kota Bandung - Naira Sahda Ranupatma; Salma Fauziah; Bilqis Putri Anas; Maulia Depriya Kembara (Pusat Riset dan Inovasi Nasional, 2024)
Pancasila should serve as guiding principle for the Indonesian people, with its meaning understood from an early age. The noble values embedded in Pancasila play a crucial role in shaping the nation's character and morals, and in filtering external cultural influences, including technological advancements. Especially in the era of globalisation, it is important to ensure that the nation's young generation is able to filter the information they receive using the values of Pancasila. In this case, the author observed 4th grade students at SDN Harapan 2 in Bandung City, West Java, through a qualitative-descriptive research method analysed using inductive techniques. This research aims to determine the level of understanding and problems faced by students in understanding Pancasila at the school. The method of implementation included a short presentation accompanied by a game-based question and answer session to keep the children enthusiastic during the presentation. The result of this research is that the students have sufficient understanding of the state symbol, the points of Pancasila, and its implementation in daily life. However, the author found several problems that need further research related to students' knowledge of the national anthem and indications of verbal bullying that are often carried out by students